In Situ Electrochemical Formation of Oxo-Functionalized Graphene on Glassy Carbon Electrode with Chemical Fouling Recovery and Antibiofouling Properties for Electrochemical Sensing of Reduced Glutathione - Chunying Xu; Gang Li; Liju Gan; Baiqing Yuan (MDPI AG, 2022)
Electrochemical detection can be used to achieve intracellular or in vivo analysis of reduced glutathione (GSH) in tissues such as brain by using a microelectrode, which can help to better understand the complex biochemical processes of this molecule in the human body. The main challenges associated with electrochemical GSH detection are the chemical fouling of electrodes, caused by the oxidation product of GSSG, and biofouling due to the non-specific absorption of biological macromolecules. Oxo-functionalized graphene was generated in situ on the surface of a glassy carbon electrode using a green electrochemical method without using any other modifiers or materials in a mild water solution. The fabricated oxo-functionalized graphene interface was characterized by Raman spectroscopy, X-ray photoelectron spectroscopy, electrochemistry, electrochemical impedance spectroscopy, and contact angle measurements. The interface showed high electrocatalytic activity towards the oxidation of GSH, and a simple and efficient GSH sensor was developed. Interestingly, the electrode is reusable and could be recovered from the chemical fouling via electrochemical oxidation and reduction treatment. The electrode also exhibited good antibiofouling properties. The presented method could be a promising method used to treat carbon materials, especially carbon-based microelectrodes for electrochemical monitoring of intracellular glutathione or in vivo analysis.